Selecting the right drug. Issue 8 (August 2013) - Avery, Tony; Gookey, Gill; Spencer, Rachel; Knox, Richard; Marsden, Kate; Salema, Ndeshi
Around 1 in 10 of the prescribing errors detected in the General Medical Council-funded PRACtICe study involved incorrect drug selection or unnecessary prescriptions. In this article we focus on the principles involved in selecting the right drug for individual patients. We also highlight the usefulness of prescribing formularies and explain when it is appropriate to prescribe generically and when it is necessary to prescribe by brand. The article gives the reader opportunities to reflect upon different scenarios involving prescribing decisions, and there are also suggestions for additional continuing professional development activities.